Factors Influencing the Decline of Students’ Motivation in Higher Education Speaking Classes at the University of Riau Kepulauan. - Tantri Niwanda; Desi Surlitasari Dewi; Adam Adam (Universitas Islam Ogan Komering Ilir Kayuagung, 2026)
Speaking motivation plays a fundamental role in second language learning; however, many students experience a decline in motivation when participating in speaking classes. This study aims to investigate the contributing factors behind this decline by focusing on classroom environment, teaching methods, lecturer behavior, and students’ self-confidence. A qualitative descriptive approach was employed, involving the distribution of questionnaires to 35 students and semi-structured interviews with 8 selected participants. The questionnaire findings reveal that a lack of confidence is the dominant factor, affecting 62% of respondents, who reported feeling fear of making mistakes, embarrassment, and anxiety when speaking English. The classroom environment was also influential, with 53% of respondents stating that noise, discomfort, and poor facilities reduced their motivation. Additionally, 52% agreed that monotonous instructional strategies contributed to boredom, while 48% indicated that lecturer behavior affected their willingness to participate. The interview data further support these results, showing that psychological discomfort and limited interaction negatively affect participation. Overall, the findings indicate that both internal and external factors contribute to demotivation in speaking classes. Therefore, lecturers need to create a supportive learning atmosphere, apply varied interactive teaching methods, and provide positive feedback to help students develop confidence and enhance motivation.